Arterial hypertension - Polskie Towarzystwo Nadciśnienia Tętniczego (Via Medica, 2015)
Original articles, case reports, novel drugs presentations as well as review and editorial articles in the field of hypertension, and cardiovascular medicine.
Keywords: Hypertension : Periodicals; Hypertension : Treatment : Periodicals; Hypertension; Hypertension : Treatment